Comparative Evaluation Of Postoperative Sensitivity Using Total-Etch Versus Self-Etch Bonding Techniques In Resin Composite Restorations: A Randomized Clinical Trial - Shahid Ahmad Marwat; Hassan Maqbool; Umair ul Haq; Zarnab Rizwan; Khadija Sajid; Shakeel Ur Rehman Khattak (Journal of Rawalpindi Medical College)
Objective: To assess and compare postoperative sensitivity in resin composite restorations using the self-etch versus total-etch technique.